APPLICATION DES MÃ‰THODES Dâ€™ANALYSES STATISTIQUES MULTIVARIÃ‰ES Ã€ Lâ€™Ã‰TUDE DES CARACTÃ‰RISTIQUES PHYSICOCHIMIQUES DES SOLS DE SAÃS, MAROC (APPLICATION OF MULTIVARIATE STATISTICAL ANALYSIS METHODS TO THE STUDY OF PHYSICO-CHEMICAL CHARACTERISTICS OF SOILS SAÃS, - Touhtouh, D.; EL Halimi, R.; Moujahid, Y.; El Faleh, E.M. (European Scientific Journal, ESJ, 2014)
The Sais is the most famous agricultural region in Morocco by the diversity of its soil classes. The data on the physico-chemical characteristics of the three main soil types in this region, have been the subject of a detailed statistical analysis (principal component analysis (PCA) and hierarchical classification). Our database relating to these floors, consists of quantitative variables 14 and 32 individuals. The eigenvalue analysis has retaining pins which contain the highest percentage of the information from the data table. The implementation of the CPA, the soils studied, helped highlight the dominance of the clay fraction and exchangeable bases in the Vertisols, which explains their high cationic exchange capacity (CEC). By cons, it is very low in fersialitic soils. Indeed, in these soils, it is the sands are the most explanatory variable. Finally the class Calcimagnesic soil is characterized by a high total limestone and organic matter.